2013
DOI: 10.5213/inj.2013.17.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Trial Without Catheter for First Spontaneous Acute Urinary Retention

Abstract: PurposeTo find the association of trial without catheter (TWOC) outcome for first spontaneous acute urinary retention (AUR) in benign prostatic obstruction with age, prior lower urinary tract symptoms (LUTS), retention volume at catheterization (RV), and size of prostate.MethodsOur prospective observational analytical (interventional) study enrolled 77 cases of spontaneous AUR over 24 months. After clinical evaluation, digital rectal examination, and transabdominal ultrasonography, all patients were catheteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
2
4
1
Order By: Relevance
“…T h i s i s compatible with the findings of previous related studies. 6,7 Our TWOC rate for alfuzosin (57.1%) was comparable to that of a larger scale study conducted by McNeil et al 8 Mahadik et al 9 demonstrated strong association between age, prostate size on ultrasound and TWOC outcome. Contrary to their findings, we did not find significant association between age and prostate size in fingerbreadth with TWOC rate.…”
Section: Discussionsupporting
confidence: 82%
“…T h i s i s compatible with the findings of previous related studies. 6,7 Our TWOC rate for alfuzosin (57.1%) was comparable to that of a larger scale study conducted by McNeil et al 8 Mahadik et al 9 demonstrated strong association between age, prostate size on ultrasound and TWOC outcome. Contrary to their findings, we did not find significant association between age and prostate size in fingerbreadth with TWOC rate.…”
Section: Discussionsupporting
confidence: 82%
“…12,13 On the contrary Mahadik, Zeif and Lim et al in their studies of 58, 100 and 79 patients each found RUV to be a statistically insignificant parameter (mean RUV of 850 ml, 750 ml and 800 ml respectively). 11,14,15 PV was not found to be a parameter of statistical significance in our study. Literature is divided with respect to this.…”
Section: Discussioncontrasting
confidence: 71%
“…Several studies investigating factors for successful catheter removal found prostate volume and age as significant predictors for successful catheter removal [9,18,20,22,23]. In the present study, predictive value for these parameters was also high.…”
Section: Discussionsupporting
confidence: 63%
“…Most of the other studies did not define a residual volume cutoff when assessing successful catheter removal. Only Mahadik et al [20] characterized a successful catheter removal when residual urine volume was <200 ml. In our opinion, it has to be considered that consistent high residual urine volumes have the risk of other urological complications like urinary tract infections or chronic hydronephrosis leading to loss of kidney function.…”
Section: Discussionmentioning
confidence: 99%